Phase-change artificial aggregate and preparation method thereof

By using phase change microcapsule technology and the coating of resin and cement layers in concrete, the problems of uneven impregnation and leakage of phase change materials in concrete are solved, and efficient heat storage and stable performance of phase change artificial aggregates are achieved.

CN119750938APending Publication Date: 2025-04-04SHENZHEN UNIV

Patent Information

Application Number
CN202411766234.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the prior art adds phase change material to concrete, it is difficult to ensure the stable impregnation depth and distribution uniformity of the phase change material, and leakage and failure of the phase change material are prone to occur.

Method used

The phase change microcapsule technology is used to wrap the phase change material in the microcapsule, and these microcapsules are added to the artificial aggregate core, and then the artificial aggregate core is coated with the resin and cement layer to form the phase change artificial aggregate.

Benefits of technology

Through the protection of microcapsules, the phase change material is ensured not easily leaked during the phase change process, which improves performance stability and service life, and further prevents leakage and failure of the phase change material by coating the resin and cement layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750938A_ABST
    Figure CN119750938A_ABST
Patent Text Reader

Abstract

The invention discloses a phase-change artificial aggregate and a preparation method thereof, and relates to the field of concrete. The phase-change artificial aggregate comprises an artificial aggregate core body, a resin layer coated on the surface of the artificial aggregate core body and a cement layer coated on the surface of the resin layer, and the artificial aggregate core body comprises building waste, phase-change microcapsules and cement. The phase-change artificial aggregate provided by the invention can consume the building waste and reduce the accumulation of the building waste, the phase-change material is not easy to leak, has enough strength and phase-change heat storage capacity, can replace natural aggregate, and has stronger practicability as a building aggregate material. And the concrete is more suitable for being applied to concrete of a building envelope structure with heat storage and heat release functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete, and in particular to a phase-change artificial aggregate and a preparation method thereof. Background Art

[0002] The material with the greatest demand in the construction industry is concrete. Concrete is generally made by mixing cement, aggregates, water, mineral admixtures and some additives. Aggregates (mainly sand, stone, etc.) are used in large quantities, accounting for about 60% to 70% of the total concrete. With the over-exploitation of mines, natural sand and gravel aggregate resources are becoming increasingly scarce. Therefore, there is an urgent need to develop artificial aggregates to replace natural sand and gravel aggregates.

[0003] In addition, in recent years, the carbon emission problem caused by the use of traditional energy to meet energy demand in buildings has become increasingly serious. Reducing the energy consumption of buildings for heating or cooling is the key to improving the energy efficiency of buildings. The implementation method is to combine phase change materials that can store and release heat energy with the concrete of the building envelope. When the ambient temperature is higher than the melting point of the phase change material, the phase change material changes from solid to liquid by absorbing excess heat, and solidifies when the temperature drops, while releasing heat into the room. Phase change materials maintain an almost constant temperature during the physical state transition to prevent internal overheating or overcooling. Integrating phase change materials into buildings can enhance the heat storage effect and improve thermal comfort, reduce energy consumption of electrical appliances such as air conditioners, and improve energy utilization efficiency. However, the traditional phase change materials currently added to concrete generally use porous natural materials as phase change material carriers, and use the immersion method to load the phase change material. This method cannot ensure that the phase change material maintains a stable impregnation depth and uniform distribution in the carrier, and the phase change material is prone to leakage and failure during the phase change process.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a phase change artificial aggregate and a preparation method thereof, aiming to provide a phase change artificial aggregate that can consume construction waste, reduce the accumulation of construction waste, and is not prone to leakage and failure of phase change materials, so as to replace natural aggregates for use in concrete of building envelope structures.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a phase change artificial aggregate, wherein the phase change artificial aggregate comprises an artificial aggregate core, a resin layer coated on the surface of the artificial aggregate core, and a cement layer coated on the surface of the resin layer, and the artificial aggregate core comprises construction waste, phase change microcapsules and cement.

[0008] Optionally, in the artificial aggregate core, the mass ratio of the construction waste, cement and phase change microcapsules is (60-90):(9-15):(16-28).

[0009] Optionally, in the artificial aggregate core, the construction waste includes cement paste waste, and the cement includes ordinary Portland cement. Optionally, the cement paste waste includes the following chemical elements in mass content:

[0010] Na 0.124%~0.128%, Mg 2.641%~2.731%, Al 3.612%~3.742%, Si14.864%~15.757%, P 0.029%~0.035%, S1.785%~1.795%, Cl 0.069%~0.073%, K 0.916%~0.981%, Ca 69.281%~70.907%, Ti 0.256%~0.266%, Mn 0.104%~0.118%, Fe 4.308%~4.905%, Cu 0.012%~0.023%, Zn 0.13%~0.17%, Rb0.008%~0.012%, Sr 0.025%~0.037%, Zr 0.01%~0.02% and Pb 0.056%~0.069%.

[0011] Optionally, the phase-change microcapsule comprises a capsule shell and a phase-change material in the capsule shell, the capsule shell material comprises at least one of silicon dioxide, polymethyl methacrylate and melamine formaldehyde, and the phase-change material comprises at least one of paraffin, stearic acid and lauric acid;

[0012] The resin layer includes at least one of epoxy resin, polyurethane resin and acrylic resin;

[0013] The cement layer comprises ordinary Portland cement.

[0014] Optionally, the particle size of the artificial aggregate core is 4.75-20 mm.

[0015] The second aspect of the present invention provides a method for preparing the phase change artificial aggregate as described above, wherein the phase change artificial aggregate is prepared by a cold bonding granulation method, and the method for preparing the phase change artificial aggregate comprises the following steps:

[0016] Mixing construction waste with cement to obtain a mixture;

[0017] A part of the mixed material is mixed with the phase change microcapsules and placed in a disc granulator for granulation; then the remaining part of the mixed material is added to the disc granulator, and granulation is continued. After curing, an artificial aggregate core is obtained;

[0018] The resin is coated on the surface of the artificial aggregate core to form a resin layer;

[0019] The surface of the resin layer is coated with cement to form a cement layer, thereby obtaining the phase-change artificial aggregate.

[0020] Optionally, the step of mixing construction waste with cement to obtain a mixture specifically includes:

[0021] The construction waste is crushed, and then the crushed construction waste is mixed with cement in a mass ratio of (60-90):(9-15) to obtain a mixture.

[0022] Optionally, a part of the mixture is mixed with phase change microcapsules and placed in a disc granulator for granulation; then the remaining part of the mixture is added to the disc granulator, and granulation is continued. After curing, the steps of obtaining the artificial aggregate core body specifically include:

[0023] A part of the mixture is mixed with the phase change microcapsules, placed in a disc granulator for granulation for 2 to 3 minutes, then sprayed with water, and granulation is continued for 5 minutes; then the remaining part of the mixture is added to the disc granulator, and granulation is continued for 5 minutes; then standardized curing is carried out at a temperature of 20±2°C and a relative humidity of 95% to obtain an artificial aggregate core.

[0024] Optionally, the steps of coating the surface of the artificial aggregate core with resin to form a resin layer; and coating the surface of the resin layer with cement to form a cement layer specifically include:

[0025] Providing a resin emulsion, immersing an artificial aggregate core body into the resin emulsion, and taking it out after stirring to obtain an artificial aggregate core body with the surface coated with the resin emulsion;

[0026] The artificial aggregate core body with the surface coated with resin emulsion is placed in cement powder, and taken out after the surface is coated with cement. After standing for a preset time, the resin emulsion on the surface of the artificial aggregate core body solidifies, and a resin layer is formed on the surface of the artificial aggregate core body, and a cement layer is formed on the surface of the resin layer.

[0027] Beneficial effect: The present invention adds phase change microcapsules into the inner core of artificial aggregate to improve the heat storage capacity of phase change artificial aggregate. The phase change material is incorporated in the form of microcapsules. Due to the protection of the capsule shell, the phase change material is not prone to leakage during the phase change solid-liquid conversion process, thereby ensuring performance stability and extending service life.

[0028] The traditional method is to directly mix the phase change material into concrete using porous natural materials as carriers, while the present invention mixes the phase change microcapsules into artificial aggregates, and then mixes the artificial aggregates mixed with the phase change microcapsules into concrete for application. That is, when applied, the present invention uses artificial aggregates as carriers to mix the phase change microcapsules into concrete, which can further prevent the leakage and failure of the phase change microcapsules, that is, the artificial aggregate core can protect the phase change microcapsules to a certain extent. In addition, the existing phase change materials are generally prepared by immersion using porous natural materials as carriers. The traditional immersion method is difficult to accurately control the immersion depth and distribution uniformity of the phase change material during immersion. The present invention uses phase change microcapsules to directly mix, which has better controllability and can ensure the stability of the amount of phase change material in the phase change artificial aggregate.

[0029] In addition, the coating of the resin layer and the cement layer in the present invention can further prevent leakage and failure of the phase change material. In addition, the cement in the cement layer has a certain hydration activity, which can increase the interface bonding force between the phase change artificial aggregate and the cement paste in the concrete, ensuring that the concrete mixed with the phase change artificial aggregate has good overall strength, and the thermal conductivity of the cement layer is higher than that of the resin layer, which can further improve the overall thermal conductivity of the phase change artificial aggregate.

[0030] At the same time, the present invention uses an artificial aggregate core prepared from construction waste, which can reduce the accumulation of construction waste compared to traditional natural aggregates, reduce the environmental pressure of landfill and accumulation, realize the resource utilization of solid waste, save natural materials, and contribute to sustainable development. In addition, the artificial aggregate core is equivalent to adding phase change microcapsules to recycled aggregate prepared from construction waste and cement, and the recycled aggregate has better binding properties to the phase change microcapsules than natural aggregates in the process of preparing phase change artificial aggregates.

[0031] The phase-change artificial aggregate provided by the present invention has sufficient strength and phase-change heat storage capacity, can replace natural aggregate, and has stronger practicality as a building aggregate material, and is more suitable for application in concrete of building envelope structures with heat storage and heat release functions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the process for preparing phase change artificial aggregate in Example 1.

[0033] Figure 2 This is a cross-sectional view of the phase change artificial aggregate prepared after curing for 28 days in Example 1.

[0034] Figure 3 This is a graph showing the compressive strength results of the phase change artificial aggregate prepared with different curing days in Example 1 and the artificial aggregate prepared with different curing days in Comparative Example 1.

[0035] Figure 4This is a graph showing the change in heat absorption per unit mass of the phase change artificial aggregate prepared by curing for 28 days in Example 1 and the artificial aggregate prepared by curing for 28 days in Comparative Example 1 as the temperature rises. DETAILED DESCRIPTION

[0036] The present invention provides a phase change artificial aggregate and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0038] An embodiment of the present invention provides a phase change artificial aggregate, wherein the phase change artificial aggregate includes an artificial aggregate core, a resin layer coated on the surface of the artificial aggregate core, and a cement layer coated on the surface of the resin layer, and the artificial aggregate core includes construction waste, phase change microcapsules and cement.

[0039] The present invention adds phase change microcapsules into the inner core of artificial aggregate to improve the heat storage capacity of phase change artificial aggregate. The phase change material is incorporated in the form of microcapsules. Due to the protection of the capsule shell, the phase change material is not prone to leakage during the phase change solid-liquid conversion process, thereby ensuring performance stability and extending service life.

[0040] The traditional method is to directly mix the phase change material into concrete using porous natural materials as carriers, while the present invention mixes the phase change microcapsules into artificial aggregates, and then mixes the artificial aggregates mixed with the phase change microcapsules into concrete for application. That is, when applied, the present invention uses artificial aggregates as carriers to mix the phase change microcapsules into concrete, which can further prevent the leakage and failure of the phase change microcapsules, that is, the artificial aggregate core can protect the phase change microcapsules to a certain extent. In addition, the phase change material is generally prepared by the immersion method using porous natural materials as carriers. The traditional immersion method is difficult to accurately control the immersion depth and distribution uniformity of the phase change material during immersion. The embodiment of the present invention uses the direct incorporation of phase change microcapsules, which has better controllability and can ensure the stability of the amount of phase change material in the phase change artificial aggregate.

[0041] In addition, in the embodiment of the present invention, the coating of the resin layer and the cement layer can further prevent the leakage and failure of the phase change material, prevent the leakage of the phase change material due to the rupture of the capsule shell, and thus avoid the problem that the leakage of the phase change material affects the interface between the phase change artificial aggregate and the cement paste in the concrete, and avoid the phenomenon of poor interfacial adhesion. The cement in the cement layer has a certain hydration activity, which can increase the interfacial bonding force between the phase change artificial aggregate and the cement paste in the concrete, ensuring that the concrete mixed with the phase change artificial aggregate has good overall strength, and the thermal conductivity of the cement layer is higher than that of the resin layer, which can further improve the overall thermal conductivity of the phase change artificial aggregate.

[0042] The existing treatment of construction waste is often direct landfill, which occupies a large amount of precious land resources. The embodiment of the present invention uses an artificial aggregate core prepared from construction waste, which can reduce the accumulation of construction waste compared to traditional natural aggregates, reduce the environmental pressure of landfill and accumulation, realize the resource utilization of solid waste, save natural materials, and contribute to sustainable development. The embodiment of the present invention also provides an eco-friendly and sustainable construction waste treatment method. In addition, the artificial aggregate core is equivalent to adding phase change microcapsules to recycled aggregate prepared from construction waste and cement, and the recycled aggregate has better binding properties to the phase change microcapsules than natural aggregates in the process of preparing phase change artificial aggregates.

[0043] The phase-change artificial aggregate provided by the present invention has sufficient strength and phase-change heat storage capacity (the arrangement of the capsule shell, the artificial aggregate core, the resin layer and the cement layer provides quadruple protection for the phase-change material in the capsule shell, effectively preventing leakage of the phase-change material), can replace natural aggregate, and is more practical as a building aggregate material, and is more suitable for use in concrete of building envelope structures with heat storage and heat release functions.

[0044] Specifically, when used in the concrete of building envelope structures, when the ambient temperature rises, the phase change material in the phase change artificial aggregate produces rapid heat exchange with the environment, changing from solid to liquid, absorbing external heat, and ensuring that the indoor temperature is stable within a certain range; when the external ambient temperature drops, the phase change material in the phase change artificial aggregate changes from liquid to solid, releasing heat, maintaining the indoor temperature stable within a certain range, which can reduce the operation of temperature control equipment and reduce energy consumption.

[0045] In some embodiments, in the artificial aggregate core, the mass ratio of construction waste, cement and phase change microcapsules is (60-90):(9-15):(16-28). For example, it can be 60:9:16, 60:9:28, 70:10:16, 70:10:28, 90:9:16, 90:10:16, 90:10:20, 90:15:16 or 90:15:28.

[0046] In some specific embodiments, in the artificial aggregate core, the mass ratio of construction waste, cement and phase change microcapsules is (85-90):(10-15):(16-28).

[0047] In this embodiment, more construction waste can be consumed in the preparation of phase change artificial aggregate. At the same time, the phase change microcapsules in this dosage ratio can ensure the heat storage capacity of the phase change artificial aggregate (ensure the heat storage capacity of the concrete containing the phase change artificial aggregate). When the phase change artificial aggregate is applied to the concrete of the building envelope structure, it can maintain the indoor temperature stable within a certain range, reduce the operation of temperature control equipment, and reduce energy consumption; at the same time, compared with ordinary construction waste artificial aggregate (not containing phase change microcapsules), it has higher compressive strength.

[0048] In some embodiments, in the artificial aggregate core, the construction waste includes cement paste waste, and the cement includes ordinary Portland cement.

[0049] In some embodiments, the cement paste waste includes the following chemical elements in mass content:

[0050] Na 0.124%~0.128%, Mg 2.641%~2.731%, Al 3.612%~3.742%, Si14.864%~15.757%, P 0.029%~0.035%, S1.785%~1.795%, Cl 0.069%~0.073%, K 0.916%~0.981%, Ca 69.281%~70.907%, Ti 0.256%~0.266%, Mn 0.104%~0.118%, Fe 4.308%~4.905%, Cu 0.012%~0.023%, Zn 0.13%~0.17%, Rb0.008%~0.012%, Sr 0.025%~0.037%, Zr 0.01%~0.02% and Pb 0.056%~0.069%.

[0051] In some embodiments, the phase change microcapsule includes a capsule shell and a phase change material located in the capsule shell, the material of the capsule shell includes at least one of silicon dioxide, polymethyl methacrylate and melamine formaldehyde, and the phase change material includes at least one of paraffin, stearic acid and lauric acid.

[0052] In some specific embodiments, the material of the capsule shell is silicon dioxide, and the phase change material is paraffin wax, that is, commercial phase change paraffin wax microcapsules are selected to enhance the thermal properties of the phase change artificial aggregate.

[0053] The silica shell has good chemical stability, which can prevent the internal phase change material from chemically reacting with the external environment, causing material degradation and performance decay, thereby extending the service life of the phase change material. While preventing the leakage of the phase change material, the silica shell can also provide a certain mechanical strength.

[0054] Paraffin was chosen as the core material for phase change microcapsules because it has the following advantages: (1) high purity and extremely high latent heat of phase change, i.e., it can absorb or release a large amount of heat during phase change; and (2) it is relatively stable in alkaline environments and resistant to degradation in alkaline media such as concrete.

[0055] In some embodiments, the resin layer includes at least one of epoxy resin, polyurethane resin and acrylic resin. Specifically, the resin layer is composed of at least one of epoxy resin, polyurethane resin and acrylic resin.

[0056] In some embodiments, the cement layer comprises ordinary Portland cement. Specifically, the cement layer is composed of ordinary Portland cement.

[0057] In some embodiments, the particle size of the artificial aggregate core is 4.75-20 mm.

[0058] The embodiment of the present invention further provides a method for preparing the phase-change artificial aggregate as described above in the embodiment of the present invention, wherein the phase-change artificial aggregate is prepared by a cold bonding granulation method, and the method for preparing the phase-change artificial aggregate comprises the following steps:

[0059] S1. Mixing construction waste with cement to obtain a mixture;

[0060] S2, mixing a part of the mixture with the phase change microcapsules, and placing the mixture in a disc granulator for granulation; then adding the remaining part of the mixture to the disc granulator, continuing granulation, and curing to obtain an artificial aggregate core;

[0061] S3, coating the surface of the artificial aggregate core with resin to form a resin layer; coating the surface of the resin layer with cement to form a cement layer, thereby obtaining the phase change artificial aggregate.

[0062] The present invention adopts a cold bonding granulation method to prepare phase change artificial aggregate, which has a simple process and can realize large-scale production of phase change artificial aggregate. The prepared phase change artificial aggregate has sufficient strength and phase change heat storage capacity, and the phase change material is not easy to leak, and can replace natural aggregate for application.

[0063] In addition, the treatment of construction waste has gradually become a focus of social attention. These construction wastes mainly include excess concrete and cement paste waste from washing truck mixer drums and rework on site. The traditional treatment method for these construction wastes is direct landfill, which not only occupies a large amount of valuable land resources but also generates a large amount of landfill costs. The alkaline substances in the waste will also cause harm to the soil. In order to achieve a sustainable development strategy, these wastes are consumed for the second time. The present invention adopts cold bonding granulation technology, which has certain advantages in this regard. Specifically, cold bonding granulation is to use crushed construction waste as an auxiliary cementitious material to achieve particle agglomeration to produce artificial cold bonding aggregate, thereby replacing the natural coarse aggregate in concrete or the natural fine aggregate in mortar.

[0064] In step S1, in some embodiments, the step of mixing construction waste with cement to obtain a mixture specifically includes:

[0065] The construction waste is crushed, and then the crushed construction waste is mixed with cement in a mass ratio of (60-90): and (9-15) to obtain a mixture.

[0066] In some specific embodiments, the step of mixing construction waste with cement to obtain a mixture specifically includes:

[0067] The construction waste is crushed, and then the crushed construction waste is mixed with cement in a mass ratio of (85-90):(10-15) to obtain a mixture.

[0068] In step S2, in some embodiments, a part of the mixture is mixed with the phase change microcapsules and placed in a disc granulator for granulation; then the remaining part of the mixture is added to the disc granulator, and granulation is continued. After curing, the steps of obtaining the artificial aggregate core body specifically include:

[0069] A part of the mixture (such as 80%) is mixed with the phase change microcapsules, placed in a disc granulator for granulation for 2 to 3 minutes, and then sprayed with water (the amount is 17% to 22% of the total mass of the mixture, for example, it can be 17%, 18%, 19%, 20%, 21% or 22%, etc.), and granulation is continued for 5 minutes; then the remaining part (such as 20%) of the mixture is added to the disc granulator, and granulation is continued for 5 minutes; then standardized curing is carried out at a temperature of 20±2°C and a relative humidity of 95% to obtain an artificial aggregate core.

[0070] In some embodiments, the parameters of the disc granulator are:

[0071] The disc inclination angle is 45-60° (for example, it can be 45°, 50°, 55° or 60°, etc.), the disc diameter is 100-500cm (for example, it can be 100cm, 200cm, 300cm, 400cm or 500cm, etc.), the edge height is 15-20cm (for example, it can be 15cm, 16cm, 17cm, 18cm, 19cm or 20cm, etc.), and the rotation speed is 15-35rpm (for example, it can be 15rpm, 20rpm, 25rpm, 30rpm or 35rpm, etc.).

[0072] In step S3, in some embodiments, the steps of coating the surface of the artificial aggregate core with resin to form a resin layer; and coating the surface of the resin layer with cement to form a cement layer specifically include:

[0073] S31, providing a resin emulsion, immersing the artificial aggregate core body into the resin emulsion, stirring (for 30 to 60 seconds) and then fishing out to obtain an artificial aggregate core body with the surface coated with the resin emulsion;

[0074] S32, placing the artificial aggregate core body with the surface coated with resin emulsion in cement powder (specifically, placing the artificial aggregate core body with the surface coated with resin emulsion in cement powder before the resin emulsion on the surface of the artificial aggregate core body solidifies), stirring for 30 to 60 seconds until the surface is fully coated with cement, taking it out, and standing it for a preset time, the resin emulsion on the surface of the artificial aggregate core body solidifies and solidifies, forming a resin layer (containing cured resin, such as cured epoxy resin) on the surface of the artificial aggregate core body, and forming a cement layer on the surface of the resin layer.

[0075] In this embodiment, the resin emulsion is used to coat the artificial aggregate core, which can further improve the sealing of the phase change artificial aggregate, prevent the capsule shell of the phase change microcapsule from breaking during the preparation process, causing the phase change material to leak and affect the interface between the phase change artificial aggregate and the cement paste in the concrete, avoid the phenomenon of poor interfacial adhesion, and ensure that the phase change artificial aggregate has a higher quality. The artificial aggregate core with the surface coated with resin emulsion is placed in cement powder for coating. On the one hand, the artificial aggregate cores coated with resin emulsion can be easily separated and not easily agglomerated, making the processing process more convenient; on the other hand, cement has a certain hydration activity, which can increase the interfacial bonding force between the phase change artificial aggregate prepared by the preparation method and the cement paste in the concrete, ensuring that the concrete mixed with the phase change artificial aggregate has a better overall strength, and the thermal conductivity of cement is also higher than that of the cured resin, which can further improve the overall thermal conductivity of the phase change artificial aggregate prepared by the preparation method.

[0076] In step S31, in some embodiments, the method for preparing the resin emulsion includes the following steps: mixing a resin (such as epoxy resin), an amine curing agent (such as 1,6-hexanediamine), and a diluent (ethylene glycol glycidyl ether) in a mass ratio of 1:0.4:0.1 to obtain a resin emulsion.

[0077] In step S32, the standing time is 15 to 30 minutes, that is, the curing time is 15 to 30 minutes (for example, 15 minutes, 20 minutes, 25 minutes or 30 minutes, etc.). The above curing time can not only make it easy to separate the artificial aggregate cores coated with resin emulsion, but also minimize the leakage rate of the phase change material.

[0078] The present invention will be further described below by means of specific examples.

[0079] Example 1

[0080] In the following examples, the cement paste waste includes the following chemical elements by mass content:

[0081] Na 0.125%, Mg 2.641%, Al 3.742%, Si 15.757%, P 0.035%, S1.785%, Cl0.073%, K 0.981%, Ca 69.281%, Ti 0.266%, Mn 0.118%, Fe 4.905%, Cu 0.023%, Zn 0.13%, Rb 0.012%, Sr 0.037%, Zr 0.02% and Pb 0.069%.

[0082] The phase-change microcapsules are composed of a silicon dioxide capsule shell and paraffin in the silicon dioxide capsule shell, namely, phase-change paraffin microcapsules.

[0083] This embodiment provides a method for preparing a phase-change artificial aggregate, such as Figure 1 As shown, the following steps are included:

[0084] (1) Cement paste waste is crushed into pieces by a crusher, the pieces are dried in a drying oven at 65° C. until the mass remains unchanged, and then ground by a ball mill until they pass through a 200-mesh sieve;

[0085] (2) the cement paste waste (CSW) obtained after the treatment in step (1) and ordinary Portland cement (OPC) were uniformly mixed in a 5 L bucket at a mass ratio of 90:10 to obtain 2 kg of a mixture;

[0086] (3) 80% (mass fraction) of the mixture is mixed with phase change paraffin microcapsules (the mass ratio of cement slurry waste, cement and phase change paraffin microcapsules is 90:10:20, that is, the amount of phase change paraffin microcapsules is 0.4 kg) and poured into the disc in the disc granulator (the parameters of the disc granulator are: disc inclination angle of 45°, disc diameter of 100 cm, edge height of 15 cm, and rotation speed of 35 rpm), and the granulator is rotated for 3 minutes to mix evenly. Then, a spray bottle (or watering can) is used to spray water (amount of 400 g) on ​​the material on the disc to promote powder bonding, and the granulator is rotated for 5 minutes to generate large-sized cold-bonded aggregate. Then, the remaining 20% ​​(mass fraction) of the mixture is added and combined with the cold-bonded aggregate, and finally the granulator is rotated for 5 minutes to make the powder evenly coated. Then, the waste agglomerates are preliminarily screened out through a 4.75 mm sieve, and the remaining part is subjected to secondary granulation to obtain aggregate blanks;

[0087] (4) performing standardized curing on the obtained aggregate blanks at 20±2° C. and a relative humidity of 95% for 3 days, 7 days, and 28 days, respectively, to obtain artificial aggregate core bodies prepared with different curing days;

[0088] (5) An epoxy resin, an amine curing agent (1,6-hexanediamine) and a diluent (ethylene glycol glycidyl ether) were mixed in a mass ratio of 1:0.4:0.1 to prepare an epoxy resin emulsion.

[0089] (6) The artificial aggregate cores prepared with different curing days were immersed in 3 kg of epoxy resin emulsion and stirred for 60 seconds (they were fully coated and the surface of the artificial aggregate core was covered with epoxy resin emulsion), then taken out and placed in a basin containing 10 kg of cement powder and stirred for 45 seconds until the surface was fully coated with cement. After being taken out and left to stand at room temperature for 30 minutes, the epoxy resin emulsion solidified and cured, and an epoxy resin layer was formed on the surface of the artificial aggregate core, and a cement layer was formed on the surface of the epoxy resin layer, thereby obtaining phase change artificial aggregates prepared with different curing days (3 days, 7 days and 28 days).

[0090] Comparative Example 1

[0091] This comparative example provides a method for preparing an artificial aggregate, which is different from Example 1 only in that no phase-change paraffin microcapsules are added, and artificial aggregates prepared with different curing days (3 days, 7 days and 28 days) are obtained.

[0092] test:

[0093] (1) The cross-sectional view of the phase change artificial aggregate prepared after curing for 28 days in Example 1 is as follows Figure 2 As shown, it can be seen that the phase change material has multiple layers of protection to prevent leakage. The capsule shell of the phase change microcapsule wraps the core material paraffin in the middle, and the artificial aggregate core body is also coated with an epoxy resin layer and a cement layer.

[0094] (2) The compressive strength of the phase change artificial aggregate prepared with different curing days (3 days, 7 days and 28 days) in Example 1 and the artificial aggregate prepared with different curing days (3 days, 7 days and 28 days) in Comparative Example 1 is as follows: Figure 3 As shown. Among them, the control group is the artificial aggregate without adding phase change paraffin microcapsules in Comparative Example 1, and the microcapsule group is the phase change artificial aggregate with phase change paraffin microcapsules added in Example 1. It can be seen that the compressive strength of the phase change artificial aggregate prepared with different curing days after adding phase change microcapsules is improved compared with the control group without adding. The strength of the phase change artificial aggregate cured for 28 days can reach 3MPa, and the compressive strength is increased by more than 50% compared with the control group. Specifically, it is because the phase change microcapsules can serve as hydration tuberculosis sites, so that the hydration products are attached to its surface, thereby making the phase change artificial aggregate hydrated more fully, thereby improving the mechanical properties of the phase change artificial aggregate.

[0095] (3) The results of the change in the heat absorbed by the unit mass of the phase change artificial aggregate prepared by curing for 28 days in Example 1 and the artificial aggregate prepared by curing for 28 days in Comparative Example 1 as the temperature rises are shown in the figure below: Figure 4 As shown, the phase change starting temperature of the phase change artificial aggregate in Example 1 is 18.8°C, the ending phase change temperature is 25.4°C, and the heat absorbed during the phase change process is 15 J / g. Compared with ordinary artificial aggregates, it can better adjust the environmental heat change within the temperature range suitable for the human body.

[0096] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A phase change artificial aggregate, characterized in that: The phase-change artificial aggregate comprises an artificial aggregate core, a resin layer coated on the surface of the artificial aggregate core and a cement layer coated on the surface of the resin layer. The artificial aggregate core comprises construction waste, phase-change microcapsules and cement.

2. The phase change artificial aggregate according to claim 1, characterized in that: In the artificial aggregate core, the mass ratio of the construction waste, cement and phase change microcapsules is (60-90):(9-15):(16-28).

3. The phase change artificial aggregate according to claim 2, characterized in that: In the artificial aggregate core, the construction waste includes cement paste waste, and the cement includes ordinary Portland cement.

4. The phase change artificial aggregate according to claim 3, characterized in that: The cement paste waste includes the following chemical elements by mass content: Na 0.124%~0.128%, Mg 2.641%~2.731%, Al 3.612%~3.742%, Si14.864%~15.757%, P 0.029%~0.035%, S1.785%~1.795%, Cl 0.069%~0.073%, K 0.916%~0.981%, Ca 69.281%~70.907%, Ti 0.256%~0.266%, Mn 0.104%~0.118%, Fe4.308%~4.905%, Cu 0.012%~0.023%, Zn 0.13%~0.17%, Rb 0.008%~0.012%, Sr0.025%~0.037%, Zr 0.01%~0.02% and Pb 0.056%~0.069%.

5. The phase change artificial aggregate according to claim 1, characterized in that: The phase-change microcapsule comprises a capsule shell and a phase-change material in the capsule shell, wherein the material of the capsule shell comprises at least one of silicon dioxide, polymethyl methacrylate and melamine formaldehyde, and the phase-change material comprises at least one of paraffin, stearic acid and lauric acid; The resin layer includes at least one of epoxy resin, polyurethane resin and acrylic resin; The cement layer comprises ordinary Portland cement.

6. The phase change artificial aggregate according to claim 1, characterized in that: The particle size of the artificial aggregate core is 4.75-20 mm.

7. A method for preparing the phase change artificial aggregate according to claim 1, characterized in that: The phase-change artificial aggregate is prepared by a cold bonding granulation method, and the preparation method of the phase-change artificial aggregate comprises the following steps: Mixing construction waste with cement to obtain a mixture; A part of the mixed material is mixed with the phase change microcapsules and placed in a disc granulator for granulation; then the remaining part of the mixed material is added to the disc granulator, and granulation is continued. After curing, an artificial aggregate core is obtained; The resin is coated on the surface of the artificial aggregate core to form a resin layer; The surface of the resin layer is coated with cement to form a cement layer, thereby obtaining the phase-change artificial aggregate.

8. The preparation method according to claim 7, characterized in that: The steps of mixing construction waste with cement to obtain a mixture specifically include: The construction waste is crushed, and then the crushed construction waste is mixed with cement in a mass ratio of (60-90):(9-15) to obtain a mixture.

9. The preparation method according to claim 7, characterized in that: The steps of mixing a part of the mixture with the phase change microcapsules and placing the mixture in a disc granulator for granulation; then adding the remaining part of the mixture to the disc granulator, continuing granulation, and curing to obtain the artificial aggregate core body specifically include: A part of the mixture is mixed with the phase change microcapsules, placed in a disc granulator for granulation for 2 to 3 minutes, then sprayed with water, and granulation is continued for 5 minutes; then the remaining part of the mixture is added to the disc granulator, and granulation is continued for 5 minutes; then standardized curing is carried out at a temperature of 20±2°C and a relative humidity of 95% to obtain an artificial aggregate core.

10. The preparation method according to claim 7, characterized in that: The steps of coating the surface of the artificial aggregate core with resin to form a resin layer; and coating the surface of the resin layer with cement to form a cement layer specifically include: Providing a resin emulsion, immersing an artificial aggregate core body into the resin emulsion, and taking it out after stirring to obtain an artificial aggregate core body with the surface coated with the resin emulsion; The artificial aggregate core body with the surface coated with resin emulsion is placed in cement powder, and taken out after the surface is coated with cement. After standing for a preset time, the resin emulsion on the surface of the artificial aggregate core body solidifies, and a resin layer is formed on the surface of the artificial aggregate core body, and a cement layer is formed on the surface of the resin layer.

Citation Information

Patent Citations

  • Wooden rim for wheels

    CA69281A

  • Box cap and shoe plank holder

    CA70907A

Cited By

  • Preparation method of low-carbon phase-change energy-storage environment-friendly brick

    CN121377662A

  • Alkali-activated multi-source solid waste-based phase change heat storage aggregate and preparation thereof, and preparation method of phase change heat storage concrete

    CN122079557A

  • Alkali-activated multi-source solid waste-based phase change heat storage aggregate and preparation thereof, and preparation method of phase change heat storage concrete

    CN122079557B